Case report: Three novel variants on SLC25A13 in four infants with neonatal intrahepatic cholestasis caused by citrin deficiency - Wang, Kena; Zou, Biao; Chen, Fan; Zhang, Jianling; Huang, Zhihua; Shu, Sainan (Frontiers in Pediatrics, 2023)
Background: Neonatal intrahepatic cholestasis caused by citrin deficiency (NICCD) is a common clinical phenotype of citrin deficiency in infants. Its phenotype is atypical, so genetic testing is quite necessary for the diagnosis. Case presentation: We report 4 patients with jaundice and low body weight. Furthermore, the biochemical examination of all showed abnormal liver function and metabolic changes. DNA samples of the patients were extracted and subjected to genetic screening. All candidate pathogenic variants were validated by Sanger sequencing, and CNVs were ascertained by qPCR. The genetic screening revealed 6 variants in 4 patients, and all patients carried compound heterozygous variants of SLC25A13. Importantly, 3 variants were newly discovered: a nonsense mutation in exon17（c.1803C>G）, a frameshift mutation in exon 11(c.1141delG) and a deletion of the whole exon11. Thus, four NICCD patients were clearly caused by variants of SLC25A13. Biochemical indicators of all patients gradually returned to normal after dietary adjustment. Conclusions: Our study clarified the genetic etiology of the four infants, expanded the variant spectrum of SLC25A13, and provided a basis for genetic counseling of the family.